Explanation of Stock Returns between Traditional and Downside Beta of Capital Asset Pricing Model (CAPM) (Journal of Hama University, 2022)
This research aimed to investigate the effect of using downside beta instead of traditional beta, as a component of capital asset pricing model (CAPM), in calculating  the required  rate of return, and the explanatory power of required return equivalent downside beta to actual return, using historical data  of closing prices of the research sample companies represented by banks listed in the Damascus Stock Exchange, During the period from 1/1/2018 to 31/12/2021.The empirical results was significant, downside beta has more significance and explanatory power than traditional beta to the required rates of return, and the required  rate of return equivalent downside beta are more explanatory to the actual stock returns than the required rates of return equivalent traditional beta. The research concluded that there were statistically significant differences between the measures of traditional and downside risk, where downside beta showed higher values than traditional beta, while semi-variance measure, which expresses the total risk of the stocks, showed lower values than variance, because the positive deviations in stock returns are greater than the negative deviations, which led to a decrease in total risk of stocks, While the negative deviations in market returns greater than positive deviations, led to higher values of downside beta, i.e. higher sensitivity to market risk, and this is appropriate to the conditions of the Damascus Stock Exchange, being one of the markets that are going through decline and achieve negative returns, which enables investors to use measures of downside risk for a more accurate calculation of  rate of return that are accepted and the risk premium required under the conditions of market's decline.
Keywords: Downside beta - Downside Risk – (Minimal acceptable return) (MAR) -Semi-Variance- D-CAPM -Asymmetric Measures.